2019
DOI: 10.1111/clr.13426
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter randomized controlled trial using a novel collagen membrane for guided bone regeneration at dehisced single implant sites: Outcome at prosthetic delivery and at 1‐year follow‐up

Abstract: Objectives:To compare clinical performance of a novel resorbable non-cross-linked collagen membrane (CXP) with a reference membrane (non-cross-linked resorbable membrane; BG) for simultaneous implant placement and guided bone regeneration (GBR) at dehisced single implant sites. Materials and methods:Preliminary data from this randomized controlled trial were reported previously; this is the 12-month report. The primary outcome measure was defected height at 6 months post-GBR. Secondary outcomes included implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
3
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 30 publications
3
25
3
4
Order By: Relevance
“…Recent data have shown that even slowly resorbable graft biomaterials, such as DBBM, are associated with a substantial reduction of the grafted area at 12‐month radiographic evaluation following endosinusal augmentation procedures (Franceschetti et al., 2019). However, the magnitude of RBL observed in the present study is limited compared to that reported for implants placed with concomitant GBR or in native bone (Urban et al., 2019) and implants presenting an untreated buccal dehiscence (Jung et al., 2017).…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Recent data have shown that even slowly resorbable graft biomaterials, such as DBBM, are associated with a substantial reduction of the grafted area at 12‐month radiographic evaluation following endosinusal augmentation procedures (Franceschetti et al., 2019). However, the magnitude of RBL observed in the present study is limited compared to that reported for implants placed with concomitant GBR or in native bone (Urban et al., 2019) and implants presenting an untreated buccal dehiscence (Jung et al., 2017).…”
Section: Discussioncontrasting
confidence: 77%
“…However, the magnitude of RBL observed in the present study is limited compared to that reported for implants placed with concomitant GBR or in native bone (Urban et al, 2019) and implants presenting an untreated buccal dehiscence (Jung et al, 2017).…”
Section: Discussioncontrasting
confidence: 74%
“…Therefore, without alveolar ridge augmentation to increase the buccal width and coronal height, the dental implant will assume a more lingual or palatal position, resulting in a poor emergence profile or even overhang prosthesis. Hence, an alveolar ridge augmentation before dental implant treatment is necessary to facilitate a favorable prosthetic position of the dental implant [29,30]. Notably, the cumulative success rate and survival rate of dental implants in the native bone and regenerative bone were similar [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Arguably, the chosen time frame of re‐entry might have influenced the results. Although there is no clear guideline on when to perform abutment connection after a GBR procedure, most studies performed second‐stage surgery after 6 months (Urban et al, ; Van Assche et al, ). A second shortcoming of the present study is the lack of information on soft tissue characteristics such as thickness, keratinization and attachment.…”
Section: Discussionmentioning
confidence: 99%